CHANGING BODY POSTURE AND WORKING SYSTEM IMPROVES WOKERS PERFORMANCE AND PRODUCT QUALITY - Surata, I Wayan; Manuaba, A.; Adiputra, N.; Sutjana, D.P. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 5, No. 1 Januari 2011, 2012)
Seaweed is one of the nation’s potential marine commodities that maycontribute to the national revenue and a new source of income for the localcommunity, as the cultivation of seaweed is much easier and cheaper than paddycrop, because neither pesticides nor fertilizer would be required. Other advantages ofcultivating seaweed are the fact that it can be carried out throughout the year, and itsrelatively shorter duration to reach the harvesting time. Local practice of drying theseaweed is by spreading it over a plastic sheet on the ground and exposing it to thesun. Unfortunately, such traditional practice of drying seaweed has led to increasedrisk of contamination of seaweed by dust and sand particles and other impurities.The quality of seaweed is influenced by the type of seedlings, harvesting age, andthe crucial process of drying. The local traditional working posture during drying issquatting and stooping to flatten and spread evenly the seaweed. Our preliminarystudy has shown that the farmers have had considerable musculoskeletal complaintsand fatigue with the seaweed quality being still relatively low.This study was conducted to examine the effects of changing the workers’working posture and limiting lift weight at 23 kg and introduced a 5-minute breakafter an-hour work with the aim to improve both workers’ performance and seaweedquality and productivity. This is an experimental study using a two-period crossoverdesign on 20 farmers of seaweed cultivation in the Ped Village of Nusa Penida.The results of our study showed that redesigning and changing the workers’working posture and working system improved the performance of seaweed farmersas revealed by the decrease of musculoskeletal complaints to 56.15% (p < 0.05); bydecrease in general fatigue to 50.84% (p < 0.05); by the increase in productivity to37.93% (p < 0.05), and by the increase in income to 41.62% (p < 0.05). The qualityof the dried seaweed was also improved as could be seen from the decrease in watercontent to 29.24% (p < 0.05) and decrease in impurities to 33.33% (p < 0.05).From our data it could be inferred that changing the workers’ working bodyposture and working system significantly improved both their performance and thequality of their product.
Keywords: redesign and change, working body posture, working system, seaweed quality